As mulheres nas magistraturas: Uma análise das representações sociais - Madalena Duarte; Ana Oliveira; Paula Fernando; Conceição Gomes (e-cadernos ces)
In recent decades, increasing feminization caused a significant transformation of legal professions. If until 1974 the judiciary was a profession forbidden to women, in 2014, in a total of 1784 judges, 1041 were women (58%). These numbers, as well as the growing role of some female magistrates, have raised the interest of the media and even of some judicial sectors which have promoted internal debates on the issue. However, whereas in other countries we can find several studies on this field, in Portugal analysis is still scarce. As a result, the social interpretation on the feminization of the judiciary is based mainly on speculation and often on stereotyped ideas. Seeking to contribute to fill this gap in sociolegal studies, the purpose of this paper is to look into? the social perceptions on the role of women in the Portuguese legal system.